2019
DOI: 10.1007/s13193-018-0860-5
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Sarcomas: Experience from a Tertiary Cancer Care Center from India

Abstract: Uterine sarcomas are uncommon and aggressive tumors comprising 3-7% of all uterine malignancies. The aim is to evaluate clinical presentation, histopathologic pattern, recurrence pattern, and outcome of patients with uterine sarcomas presenting to a tertiary care cancer center over an 8-year period. A total of 11 cases of uterine sarcoma were diagnosed. The median age of patients at presentation was 51 years (range 30-67 years). Six patients had leiomyosarcoma (54.5%), 4 had endometrial stromal sarcoma (36%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…However, it has been reported that additional therapeutic interventions may yield controversial results (20,24). In the present study, only 1 out of 21 patients treated primarily with radiotherapy and/or chemotherapy without surgery, exhibited a satisfactory clinical response, highlighting the poor response of these cases to the standard radiotherapy treatment, which has been previously shown (14,21,25). An additional factor, which was indicative of the aggressiveness of sarcomas and possibly of the delay for diagnosis and management, was the lack of treatment noted in the six untreated cases, which was due to the advanced stage of the disease.…”
Section: Discussionsupporting
confidence: 60%
“…However, it has been reported that additional therapeutic interventions may yield controversial results (20,24). In the present study, only 1 out of 21 patients treated primarily with radiotherapy and/or chemotherapy without surgery, exhibited a satisfactory clinical response, highlighting the poor response of these cases to the standard radiotherapy treatment, which has been previously shown (14,21,25). An additional factor, which was indicative of the aggressiveness of sarcomas and possibly of the delay for diagnosis and management, was the lack of treatment noted in the six untreated cases, which was due to the advanced stage of the disease.…”
Section: Discussionsupporting
confidence: 60%
“…A case series of 11 patients with the diagnosis of uterine sarcoma reported a median survival of 6.5, 18, and 56 months for LMS, ESS, and AS, respectively, with a 5-years OS of only 20%. 12 Similar outcomes were reported in a retrospective study on 61 patients with a median OS of 31.07 months, but their cohort included patients with Ewings sarcoma and rhabdomyosarcoma in addition to LMS, HGESS, and UES. 13 Longest survival was reported for ESS and shortest for carcinosarcoma in a retrospective study on 42 patients.…”
Section: Discussionmentioning
confidence: 56%
“…Two patients with ESS were stage 1, and 2 patients with ESS were stage 4 and the patient with AS was stage 1 in their study group. Apart from our study there was no patient with USS (19) . Kyriazoglou et al retrospectively analyzed patients treated for uterine sarcomas in their institution over a period of 17 years.…”
Section: Tab 4 the Treatment Modality And Recurrence Pattern Of Patmentioning
confidence: 67%